2019
DOI: 10.1093/jamia/ocz106
|View full text |Cite
|
Sign up to set email alerts
|

Assessing clinical heterogeneity in sepsis through treatment patterns and machine learning

Abstract: Objective To use unsupervised topic modeling to evaluate heterogeneity in sepsis treatment patterns contained within granular data of electronic health records. Materials and Methods A multicenter, retrospective cohort study of 29 253 hospitalized adult sepsis patients between 2010 and 2013 in Northern California. We applied an unsupervised machine learning method, Latent Dirichlet Allocation, to the orders, medications, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…First, our data highlight the often described, but poorly characterized, challenge of identifying and treating sepsis patients because of heterogeneity in clinical presentation ( 40 , 46 ). Compared with heart failure and stroke, which showed similarly predominant symptoms between patients, infectious patients presented with symptoms were diverse and nonspecific.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…First, our data highlight the often described, but poorly characterized, challenge of identifying and treating sepsis patients because of heterogeneity in clinical presentation ( 40 , 46 ). Compared with heart failure and stroke, which showed similarly predominant symptoms between patients, infectious patients presented with symptoms were diverse and nonspecific.…”
Section: Discussionmentioning
confidence: 82%
“…We identified key inpatient adverse outcomes (hospital mortality, the need for ICU admission during hospitalization) to assess their association with specific signs and symptoms ( 38 , 39 ). We also quantified the time to first antibiotic (grouped as ≤ or >3 hr after ED presentation) as a common sepsis process measure ( 3 , 40 ). We used multivariable logistic regression to estimate the association between the presence of each symptom and each outcome, adjusting for the presence or absence of all other signs and symptoms at a hospitalization level.…”
Section: Methodsmentioning
confidence: 99%
“…1). Three studies used an unsupervised clustering approach for clustering sepsis patients [31,42,44]. Data from sepsis patients were also used to learn optimal treatment by reinforcement learning [19].…”
Section: Machine Learning Techniques In Usementioning
confidence: 99%
“…In contrast to supervised ML models, unsupervised approaches for cluster analysis were used by only three studies identified in our review [31,42]. All three focused on sepsis patients.…”
Section: Outcome and Data Complexitymentioning
confidence: 99%
See 1 more Smart Citation